2019
DOI: 10.3390/su11195221
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges for Meeting the UN 2030 Agenda in the Light of Global Change—A Case Study of Swedish Perspectives

Abstract: This study explores how geopolitical aspects can affect actors’ sense of agency to achieve the UN 2030 Agenda for Sustainable Development and its ambition to transform the world sustainably by studying the linkages between global change and the 2030 Agenda as described by Swedish change agents. Sweden has a self-declared ambition for leadership in the 2030 Agenda. The world’s high-income countries, including Sweden, have been given a specific responsibility to achieve the Sustainable Development Goals. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The following aspects turned out as the most perspective: social needs, goals and objectives, social drivers and indicators, social challenges, social values, improvement, and development. Authors indicated current world development trends, focusing on social improvement and development, social organization and transformation (Eliasson et al, 2019;Yadav et al, 2020). It justified that the social character seems obvious, perspective, sustainability issue in the social security context.…”
Section: Discussionmentioning
confidence: 99%
“…The following aspects turned out as the most perspective: social needs, goals and objectives, social drivers and indicators, social challenges, social values, improvement, and development. Authors indicated current world development trends, focusing on social improvement and development, social organization and transformation (Eliasson et al, 2019;Yadav et al, 2020). It justified that the social character seems obvious, perspective, sustainability issue in the social security context.…”
Section: Discussionmentioning
confidence: 99%
“…Together, the "2030 Agenda for Sustainable Development", with its 17 established SDGs, and the signed "Paris Climate Agreement", which aims for the prevention of human-caused global warming and climate change, represent a comprehensive framework for achieving sustainable development [4,5]. Companies must play a key role in achieving these goals, especially those acting globally within international markets [6]. Companies indicate their individual progress and contribution via sustainability reporting and sustainability ratings [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the end, the question of when a business is truly sustainable needs to be addressed [32]. Also, in practice, the concept of societal transformation takes on largely different meanings for different actors across societies, for example, regarding pace, scope, goal and governability of transformations [33].…”
Section: Introductionmentioning
confidence: 99%